2019
DOI: 10.1002/ccr3.2432
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of vasa previa and the course of the cord vessels contribute to the safety of cesarean sections: A case report

Abstract: Vasa previa can occur even in cases without placental malposition and the precise diagnosis of vasa previa, and the course of the cord vessels contributes to a safe delivery. The color Doppler is a useful and easy‐to‐use device to confirm the presence of vasa previa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Vasa previa can also be found in women with normal placental location; however, this is very rare. In these cases, a detailed transabdominal scan with color Doppler can detect the communicating vessel in the lower uterine segment, thus reducing the risk of bleeding during Cesarean section [61][62][63] .…”
Section: Vasa Previamentioning
confidence: 99%
“…Vasa previa can also be found in women with normal placental location; however, this is very rare. In these cases, a detailed transabdominal scan with color Doppler can detect the communicating vessel in the lower uterine segment, thus reducing the risk of bleeding during Cesarean section [61][62][63] .…”
Section: Vasa Previamentioning
confidence: 99%
“…Thereby, if there was just no obvious blood flow at the time gap during ultrasonic scanning, the vasa previa could still not be identified [10] . MRI can be an alternative in identifying vasa previa, if the ultrasound scanning results are contradictory [11] . MRI has some advantages in this field [12].…”
Section: Discussionmentioning
confidence: 99%
“…If foetal vessels are running on the anterior lower segment of the uterus, obstetricians should be careful to avoid intraoperative rupture of foetal vessels. Aoki et al reported a case of vasa praevia in which the cord vessels were running on the anterior lower uterine segment [5]. They made a horizontal incision on the uterine fundus to avoid rupture of the cord.…”
Section: Discussionmentioning
confidence: 99%